2011
DOI: 10.1111/j.1745-3933.2011.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Debris disc candidates in systems with transiting planets

Abstract: Debris discs are known to exist around many planet-host stars, but no debris dust has been found so far in systems with transiting planets. Using publicly available catalogues, we searched for infrared excesses in such systems. In the recently published Wide-Field Infrared Survey Explorer (WISE) catalogue, we found 52 stars with transiting planets. Two systems with one transiting "hot Jupiter" each, TrES-2 and XO-5, exhibit small excesses both at 12 and 22 microns at a > 3 sigma level. Provided that one or bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 40 publications
3
25
1
Order By: Relevance
“…For TrES-2 (KIC 11446443) we do not detect excess in W3 with high enough significance. The SDSS optical photometry coupled with the VOSA analysis confirms the lower effective temperature reported by O'Donovan et al (2006) as compared with the higher best-fit temperature found by Krivov et al (2011). That makes the observed W3 flux not so different from the photospheric value (χ 12 = 0.9) and therefore we conclude that the excess is not significant.…”
Section: Image Inspectionsupporting
confidence: 65%
See 4 more Smart Citations
“…For TrES-2 (KIC 11446443) we do not detect excess in W3 with high enough significance. The SDSS optical photometry coupled with the VOSA analysis confirms the lower effective temperature reported by O'Donovan et al (2006) as compared with the higher best-fit temperature found by Krivov et al (2011). That makes the observed W3 flux not so different from the photospheric value (χ 12 = 0.9) and therefore we conclude that the excess is not significant.…”
Section: Image Inspectionsupporting
confidence: 65%
“…This does not affect that band's fluxes and will not affect our analysis. By performing an analogous analysis, Krivov et al (2011) selected HAT-P-5, and CoRoT-8 as candidate sources with excesses in W4 and TrES-2 and XO-5 as candidates sources with excesses at W3 and W4. However, we do not confirm any of these as excess sources.…”
Section: Image Inspectionmentioning
confidence: 99%
See 3 more Smart Citations